P14.17 Surveillance for sexually transmitted infections among female sex workers in inner-city johannesburg. (13th September 2015) - Black, V; Maseko, V; Venter, FW; Radebe, F; Mullick, S; Rees, HV; Lewis, DA
Abstract : Introduction: Sexually transmitted infection (STI) surveillance informs empiric antibiotic recommendations for syndromic management. Asymptomatic STIs are an important source of new infections which increase the risk of HIV transmission and acquisition. As female sex-workers (FSW) are key HIV/STI transmitters, microbiological studies within this population provide critical HIV/STI strategic information. Methods: Female sex workers (FSW) attending a sex-worker clinic or outreach brothel services, between March and December 2014 in inner-city Johannesburg were enrolled. A questionnaire and clinical examination were completed. Specimens were collected from the throat, urethra, cervix, vagina and rectum. Laboratory investigations included (i) culture for Neisseria gonorrhoeae (NG) with susceptibility testing for cefixime and ceftriaxone, (ii) DNA amplification using a multiplex PCR for NG,   C. trachomatis (CT), M. genitalium (MG) and T. vaginalis (TV), (iii) microscopic examination for bacterial vaginosis (BV), and (iv) serological testing for syphilis, hepatitis B and HIV. Participants with STIs were treated either at the initial visit (symptomatics) or following recall (asymptomatics). Results: The mean age of the 268 enrolled FSW was 31.5(IQR 27–35) and mean duration of sex work was 4.9 years (range 2 months–30 years). Condom use was consistent among 88(32.8%) FSW. The self-reported mean number of sexual partners in the past 4 weeks was 125(range 8–440) translating to 33, 496 sex acts/month overall. HIV prevalence was 76.0%. Infectious hepatitis B was present in 13 (4.9%) and treponemal antibodies were detected in 54(20.1%). Most (73.7%) of 196 FSW tested had evidence of one or more genital tract infection with: BV 173 (88.3%), MG 57 (29.1%), NG 28 (14.3%), TV 23 (11.7%) and CT 16 (8.2%). Only 49 (25%) FSW with laboratory-confirmed infections would qualify for syndromic management. All 21 cultured gonococci were susceptible to cephalosporins. Conclusion: There is a high prevalence of HIV and STIs among those FSW tested. The majority of STIs are asymptomatic. Disclosure of interest statement: The study was funded by USAID/PEPFAR and AIDS Fonds. SD bioline tests were provided by SD diagnostics.